THE ESSENCE OF YOUTH ARTISTIC CREATION DEVELOPMENT AS A SYSTEMATIC AND LEGAL PROCESS - Bekimbetova, Dilfuza Oralbayevna (Oriental Journal of History, Politics and Law, 2025)
The article analyzes the process of development of youth artistic creativity in Uzbekistan as a systematic and legal process. Attention is paid to the aspects of the process of development of artistic creativity among youth related to the state policy, the development of art and culture. The aspects of the process of development of youth artistic creativity in Uzbekistan related to the socio-economic, political-legal, spiritual-enlightenment life of society are considered.